PENGEMBANGAN RADIO DIGITAL PEMBELAJARAN JARAK JAUH MENGGUNAKAN MODUL RPITX RASPBERRY PI - Stephanie Imelda Pella (Jurnal Media Elektro, 2022)
This study aims to develop learning media through digital radio. The research phase is divided into three parts, namely frequency planning, digital radio module development via the RPITX module, implementation, and testing. The system has a database and has a web-based user interface to make it easier for administrators to manage learning content. This system can run in two transmission modes, namely WBFM and NBFM.